Characterization of bacterial pathogens isolated from sputum of the HIV patients visiting Sukraraj Tropical and Infectious Disease Hospital, Teku, Kathmandu. - k.c.,Rooku (2019)
ABSTRACT: Lower respiratory tract infections (LRTIs) are the most frequent respiratory diseases among HIV infected people and are frequently the first clinical manifestations of the HIV infections. This was hospital based study carried out at Sukraraj Tropical and Infectious Disease Hospital from August 2017 to March 2018 with an objective to detect and correlate various bacteria causing lower respiratory tract infection among HIV patients. A total of 106 sputum samples from confirmed HIV positive cases were processed with standard microbiological method and subjected to culture on Blood, Chocolate and MacConkey agar respectively. The isolated colonies were identified on the basis of colony morphology and biochemical tests. Out of 106 sputum specimens 67 were processed for Ziehl-Neelsen (Z-N) technique and 60 samples were also processed through GeneXpert technique for detection of Mycobacterium tuberculosis. Furthermore, predesigned questionnaire was used for data collection. The data were analyzed using statistical software SPSS version 21. Out of 106 patients 24.5% (n=26) were culture positive in which Klebsiella pneumoniae (37.93%) was predominant followed by Pseudomonas aeruginosa (31.04%), Escherichia coli (17.24%), Citrobacter freundii (6.89%) and Acinetobacter spp (6.89%). High frequency of co- infection was present in patients above 26 years old. Bacteria isolated were correlated with CD4 count of HIV patients. High bacterial growth (37.78%) was found among patients with low CD4 count (< 200). Out of 67 specimens processed for Z-N staining none of the sample showed AFB. Among 60 specimens processed for GeneXpert two specimens shows the presence of Rifampicin sensitive Mycobacterium tuberculosis. Out of total isolates, 68.9% (n=20) were MDR and 45% (n=9) were found to be ESBL producer. Hence, bacteria responsible for lower respiratory tract infections in HIV patients must be screened and susceptibility testing is essential for treatment of opportunistic infections. Key words: HIV, CD4, Bacterial infection, Lower respiratory tract infection, Opportunistic infections